1954
DOI: 10.1107/s0365110x54002514
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of WAl12, MoAl12and (Mn, Cr)Al12

Abstract: The crystal structure of WAllg. has been determined from powder samples. The unit cell is bodycentred cubic and a ----7.580 A. There are two WAll~ units per cell. The space group is T~-Im3.Two W atoms are placed in special positions 0, 0, 0, ~,1 :t2, '~ and 24 A1 atoms are in positions 24(g) with y ----0.184 and z = 0.309. The calculated density is 3.88 g.cm. -a.MoAll~ and (Mn, Cr)All~ (the G phase) are isomorphous with WA119. a ----7.573 i for MoAll~ and a = 7.507 /t, for (Mn, Cr)All~.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

1977
1977
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(25 citation statements)
references
References 0 publications
0
24
1
Order By: Relevance
“…7͒. Initially the Al 12 Mo appears ͑space group I m 3, 30 aϭb ϭcϭ7.574 Å͒, followed at 600°C by the complete disappearance of fcc Al to give the Al 8 12 Mo and unreacted bcc Mo. As expected, the lattice parameters values are larger than those reported in the literature, since the latter refer to room-temperature measurements.…”
Section: B As-milled Powders Versus Annealingcontrasting
confidence: 46%
See 1 more Smart Citation
“…7͒. Initially the Al 12 Mo appears ͑space group I m 3, 30 aϭb ϭcϭ7.574 Å͒, followed at 600°C by the complete disappearance of fcc Al to give the Al 8 12 Mo and unreacted bcc Mo. As expected, the lattice parameters values are larger than those reported in the literature, since the latter refer to room-temperature measurements.…”
Section: B As-milled Powders Versus Annealingcontrasting
confidence: 46%
“…This intermetallic, isostructural with Al 12 W, is the first-order approximant for describing the relationship between icosahedral quasicrystals and their related crystalline structures. 30,33 This point has been discussed separately in another paper. 34 Annealing of the specimen after 57 h of MA ͑Fig.…”
Section: B As-milled Powders Versus Annealingmentioning
confidence: 96%
“…It can also be considered as a filled WAll2-type structure (Adam & Rich, 1954) where La and P correspond to W and A1 and Fe occupies octahedral P interstices which are empty in WAll2. The derivation of the three structure types from the ReO a and CaTiO3-type structures is summarized in Fig.…”
Section: Geometric Relationsmentioning
confidence: 99%
“…The dispersoid system was seen to develop through the sequence solid solution --~ I phase --~ a phase --~ All2Mn with characteristic orientation relationships between the different structures (Hansen, Gj0nnes & Andersson, 1989) (Table 1). The stable phase All2Mn (Adam & Rich, 1954), which appears after prolonged annealing, has a body-centred cubic arrangement of 13-atom icosahedra with Mn in the centre. Electron-microscope observations indicated that AltEMn was nucleated on a-phase particles, with a definite orientation relationship.…”
Section: Introductionmentioning
confidence: 99%